2009
DOI: 10.1039/b901796h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly stable pure-silica thin-walled hexagonally ordered mesoporous material

Abstract: Hexagonally ordered mesoporous silica with a very narrow mesopore size distribution and exceptionally high stability paired with unusually thin pore walls was prepared using piperidine and cetyltrimethylammonium bromide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…OMS exhibits good hydrothermal and chemical stability. 6,7 The large pore volume (ca. 1000 mL/g) in combination with the large specific surface area (ca.…”
Section: Introductionmentioning
confidence: 99%
“…OMS exhibits good hydrothermal and chemical stability. 6,7 The large pore volume (ca. 1000 mL/g) in combination with the large specific surface area (ca.…”
Section: Introductionmentioning
confidence: 99%
“…32 To our knowledge, investigations into PPOP have mainly 33 focused on how to control the drug release, while ignoring the Mesoporous silica material (MSM) was first discovered by the 42 Mobil Corporation (Kresge et al, 1992) and it has attracted 43 substantial attention from researchers involved in many fields 44 such as nonlinear optics, catalysis, and molecular adsorption. MSM 45 have many excellent properties including good biocompatibility chemical stability (Verlooy et al, 2009 Step 1: 180 mL ethanol, 65 mL deionized water, and 4.5 mL 96 ammonia were placed in a glass container and stirred until 97 uniformly mixed. Then, 15 mL TEOS was dripped into the mixture.…”
mentioning
confidence: 99%
“…The OMS material, COK-11, developed by Verlooy et al revealed a superior stability at barely 0.9 nm wall thickness owing to a stronger condensation of the silicate units revealed with 29 Si nuclear magnetic resonance (NMR). Hydrothermal stability was determined by heating a suspension of OMS material in deionized water at 373 K for 24 h. Results show that the hydrothermal as well as the thermal stability along with durability of COK-11 were superior to MCM-41 and comparable to those of the best thick-walled OMS [14].…”
Section: Stability Of Oms Drug Formulationmentioning
confidence: 94%
“…Mellaerts et al were the first to demonstrate bioequivalency of OMS to the marketed solid dispersion product, Sporanox ® , using itraconazole loaded into Santa Barbara Amorphous (SBA-15) [12]. Furthermore, studies reporting good thermal and hydro thermal stability and providing additional promising findings drove development for this innovative drug-delivery technology [13,14].…”
Section: Reviewmentioning
confidence: 95%